Non-steroidal Anti-inflammatory Drugs (NSAIDs) Systemic Use: The Risk of Renal Failure - Bensman, Albert (Frontiers in Pediatrics, 2020)
For the pediatric nephrologist, the over-the-counter status for non-steroidal anti-inflammatory drugs (NSAIDs) is surprising due to their possible harmful side effects. These can include acute renal failure due mainly to glomerular hypoperfusion which may lead to acute tubular necrosis; more rarely in children, medullary ischemic injury and cardiovascular diseases; acute or chronic interstitial nephritis which may cause chronic renal failure. All of them may create electrolyte abnormalities: hyponatremia, hyperkaliemia, renal tubular acidosis, fluid retention causing hypertension.